Studies in Indian agriculture: the art of the possible - Etienne, Gilbert (Berkeley: University of California Press, 1968)
Agricultural development in India
Translation of L'Agriculture indienne; ou, l'Art du possible.
Bibliography: p. [333]-338.
obn 25/01/2019
Loans
Keywords: Agriculture; Agriculture and state